Development of a Biochemistry Practical E-Module Using a Project-Based Learning Model to Improve Students' Creative Thinking Skills - Mir'Atil Ulfa; Rilia Iriani; Syahmani (Chemistry Education Department of Education and Teaching Faculty, 2025)
This research and development (R&D) study aims to assess the validity, practicality, and effectiveness of the Android-based E-Module for Biochemistry Practicum developed using Construct 2. The development of this E-Module is designed to improve students' creative thinking skills. This study adopted the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research sample consisted of 27 students from the Chemistry Education Study Program, FKIP ULM Banjarmasin, Class of 2019, Class A1. The data collection methods used were test and non-test methods. The research instruments used for data collection in this analysis include essay assessments (pre-test and post-test) and questionnaires. Data analysis was conducted to measure three main aspects: validity, practicality, and effectiveness. The results showed that the developed E-Module product met all criteria: (1) Highly Valid, based on expert assessment of general aspects, content, language, and media design; (2) Highly Practical, as evidenced by the results of individual and small group trials, student and teaching assistant response questionnaires, and observation sheets; (3) Highly Effective, as indicated by the N-gain scores for students' creative thinking skills, which fall into the High category. Overall, this Android-based Project-Based Learning (PjBL) Biochemistry Practical E-Module has proven to be suitable and effective as a learning medium to enhance students' creative thinking skills.